OLHARES DE DENTRO: A REINVENÇÃO DA AMAZÔNIA PELO CINEMA AMAZONENSE CONTEMPORÂNEO. - Rafael de Figueiredo Lopes (Nepan editor, 2017)
This paper offers a reflection on audiovisual creative production in the Amazon, especially in the Brazilian state of Amazonas. Through different genres and formats, regional directors have provoked aesthetic ruptures in relation to the representation of the Amazon region and its populations. Local production is still limited and little publicized, but demonstrates its potentiality by transcending clichés, stereotypes and the subjugation to the role of peripheral creation, emerging as the centre of another context.